Association between high ambient temperature and spontaneous abortion: A systematic review and meta-analysis - Jie Xu; Haoyi Xu; Xiaoyu Zhao; Ziwei Guo; Shuangshuang Zhao; Qing Xu (Ecotoxicology and Environmental Safety)
High temperature may adversely affect pregnant women. However, inconsistent findings were existed in the published studies. This systematic review and meta-analysis were performed to clarify the effects of high-temperature exposure on spontaneous abortion (SA). Four databases including Web of Science, Cochrane Library, PubMed and EMBASE were used to search for relevant studies, the latest ones were available until June 2024. After the inclusion and exclusion for the obtained literatures, nine of which were included to finally investigate the effect of high temperature exposure on SA. As a result, maternal exposure to ambient high temperature significantly increased the risk of SA with an OR value of 1.09 (95 % CI: 1.02, 1.15). Subgroup analyses indicated that the heterogeneity observed in our findings might be mainly attributed to climate pattern. Furthermore, pregnancy women living in hot area and low-income country were more susceptible to SA when exposed to high temperature. Additionally, combining data from studies focusing on SA before 28 weeks (OR: 1.10; 95 % CI: 1.02, 1.18) showed a connection of high temperature with an elevated risk of SA. Thus, we give the conclusion that high temperature in pregnancy increase the risk of SA. Further research should more comprehensively account for the impact of climate pattern. This study offers a valuable insight into preventing SA linked to meteorological factors.